The Clinical Picture of a Bilateral Perisylvian Syndrome as the Initial Symptom of Mega-Corpus-Callosum Syndrome due to a MAST1-Gene Mutation - Hecher, Laura; Johannsen, Jessika; Bierhals, Tatjana; Buhk, Jan-Hendrik; Hempel, Maja; Denecke, Jonas (Neuropediatrics, 2020)
Congenital bilateral perisylvian syndrome (CBPS) is a rare neurological disorder associated with typical clinical and imaging features such as bilateral symmetrical polymicrogyria, either exclusively or mainly affecting the perisylvian region of the brain. We present a girl with the typical clinical picture of a CBPS and a complex migration disorder, predominantly presenting as bilateral symmetrical polymicrogyria associated with corpus callosum hyperplasia, ventricular dilation, and pontine hypoplasia. At the age of 6 months, the girl showed a profound global developmental delay, seizures refractory to treatment, and severe oromotor dysfunction. Exome analysis revealed a de novo mutation in microtubule-associated serine/threonine kinase 1 (MAST1). Recently, mutations in this gene were described in six patients with a cortical migration disorder named mega-corpus-callosum syndrome with cerebellar hypoplasia. Although all patients present the clinical and imaging features of CBPS, a clear assignment between CBPS and MAST1 mutations has not been reported yet.
Keywords: MAST1 gene; congenital bilateral perisylvian syndrome; polymicrogyria; corpus callosum hyperplasia; exome sequencing; microtubules